CONSULTING AND INVOLVING PARENTS IN PROVISION OF EDUCATIONAL SERVICES PROCESS FOR FAMILIES IN EDUCATIONAL INSTITUTIONS - Jurevičienė, Margarita; Rudytė, Kristina; Sapelyte, Odeta; Tomeniene, Laima (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The paper focuses on the issues of parents consulting and their involvement in an educational service process for families at schools. The quality of education and the effectiveness of provision of educational services are considered as an integral part of successful learning. To analyze parental opinion (N=530) towards their consulting and involvement in provision of educational service process quantitative and qualitative method of data collection have been chosen. According to the parental opinion, the content of consulting should be linked with learning achievements and motivation. Parental involvement is considered through the processes of professional orientation, prevention and organizing social events at school. Though, the fields of self-support groups, organizing teaching-learning programs for families, parental involvement in a formal educational process is considered as a challenging issue.